2016
DOI: 10.1111/trf.13770
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes with ABO antibody titer variability in a multicenter study of ABO‐incompatible kidney transplantation in the United Kingdom

Abstract: The colinearity of HA assay sensitivity with the receipt of PEx and EART limits some conclusions regarding the likely direction of causation. However, the association of differences in clinical practice with recognized perioperative complications of ABOiKTx identifies targets for further investigation and quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 40 publications
(54 reference statements)
1
32
0
Order By: Relevance
“…The agreement between the DTT applied gel card titer method and the SPRCA method for both anti‐A ( κ = 0.478) and anti‐B ( κ = 0.530) was found to be better. In the study by Bentell et al, analyses of ABO antibody titers carried out at separate laboratories have shown similar agreements, with κ values ranging from 0.34 to 0.55 . Without the use of DTT, the tube titer at AHG phase interprets the total ABO antibody and not the IgG antibody.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The agreement between the DTT applied gel card titer method and the SPRCA method for both anti‐A ( κ = 0.478) and anti‐B ( κ = 0.530) was found to be better. In the study by Bentell et al, analyses of ABO antibody titers carried out at separate laboratories have shown similar agreements, with κ values ranging from 0.34 to 0.55 . Without the use of DTT, the tube titer at AHG phase interprets the total ABO antibody and not the IgG antibody.…”
Section: Discussionmentioning
confidence: 84%
“…In this context, the ABO antibody titer not only guides the feasibility of the transplant but also warrants therapies and intervening procedures prior to transplant or prevention of antibody‐mediated rejection. Studies have shown that titer measurement is crucial and may even affect the outcomes of patients undergoing ABO‐incompatible transplants . Here lies the significance of the accurate estimation of the ABO antibody titer.…”
Section: Discussionmentioning
confidence: 99%
“…While relatively inexpensive, manual dilution is both labor intensive and subjective, conferring significant interoperator variation. For this reason, differences of less than two dilutions are generally not deemed to be significant . Unless the plasma is treated with DTT before testing, the titers assessed by gel column are generally considered to reflect a combination of IgM and IgG class antibodies .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, differences of less than two dilutions are generally not deemed to be significant. [14][15][16][17][18][19] Unless the plasma is treated with DTT before testing, the titers assessed by gel column are generally considered to reflect a combination of IgM and IgG class antibodies. 19 This is important, given that the blood bank is generally mainly concerned about the clinical effects of incompatible IgM class isoagglutinins, while transplant physicians are generally most concerned about the clinical effects of incompatible IgG class isoagglutinins.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there is variation in the measurement of ABO antibodies. This is known to be considerable, 34 and ABO antibody titres were not included in the initial registry data set.…”
Section: Discussionmentioning
confidence: 99%